2016
DOI: 10.1186/s13039-016-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 copy number variation in the context of single nucleotide polymorphisms in the human GSTM cluster

Abstract: BackgroundGSTM1 gene deletion is one of the most known copy number polymorphisms in human genome. It is most likely caused by homologous recombination between the repeats flanking the gene. However, taking into account that the deletion has no crucial effects on human well-being, and the ability of other GSTMs to compensate for the lack of GSTM1, a role for additional factors affecting GSTM1 deletion can be proposed. Our goal was to explore the relationships between GSTM1 deletion polymorphism and single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…Instead, we found multiple branches that are predominantly populated with deleted haplotypes and others with non-deleted haplotypes without notable population structuring. These observations are concordant with the recent study documenting the genetic variation in this locus in a Russian population ( Khrunin et al 2016 ). It is important to note here, however, that Neanderthal and Denisovan haplotypes, as well as the branching point for the chimpanzee reference haplotype, all cluster with the predominantly non-deleted haplotypes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, we found multiple branches that are predominantly populated with deleted haplotypes and others with non-deleted haplotypes without notable population structuring. These observations are concordant with the recent study documenting the genetic variation in this locus in a Russian population ( Khrunin et al 2016 ). It is important to note here, however, that Neanderthal and Denisovan haplotypes, as well as the branching point for the chimpanzee reference haplotype, all cluster with the predominantly non-deleted haplotypes.…”
Section: Resultssupporting
confidence: 93%
“…Even considering multiple single nucleotide variants within a single population, we were not able to impute the deletion accurately in any of the study populations (YRI, CHB, and CEU) ( Figure 3B ). This is concordant with the previous finding reported the difficulty to predict the copy number of the GSTM1 gene by the flanking haplotypes in CEU ( Khrunin et al 2016 ). As such, direct genotyping, rather than imputation, may be more robust approach to study GSTM1 deletion.…”
Section: Resultssupporting
confidence: 93%
“…3B). This is concordant with the previous finding reported the difficulty to predict the copy number of the GSTM1 gene by the flanking haplotypes in CEU (Khrunin et al 2016). As such, direct genotyping, rather than imputation, may be more robust approach to study GSTM1 deletion.…”
Section: Imperfect Linkage Disequilibrium Between the Gstm1 Deletion supporting
confidence: 91%
“…Finally, other factors such as SNPs and haplotypes in the GSTM cluster, CNV of other GST genes, such as GSTT1 , and environmental factors such as diet were not examined. A recent study identified substantial differences of SNP-based haplotype in GSTM cluster among groups of individuals with different GSTM1 CNV, suggesting a role for local genetic context in the deletion frequency thus the deletion-related effects on various disease (Khrunin et al, 2016). Studies that examined the combined effect of GSTM1 and GSTT1 deletion showed increased risk for ESRD in patients with null genotype of both GSTM1 and GSTT1 (Agrawal et al, 2007; Suvakov et al, 2013; Nomani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%